O acesso e permanência dos professores contratados nas instituições educativas : uma análise das suas experiências - Jann, Margaret (2016)
This research aimed to investigate the meanings set by teachers on temporary contracts on their teaching work from their entrance, which is made through a temporary contract, in public education in the city of Cariacica. Scholars as Gatti (2011) and Oliveira (2008) have been analyzing and discussing the transformations that the teaching work has undergone and they also point out the execution of the contract for temporary work as a reality in educational networks. In contemporary times, we have been living with economic adjustments that begin to interfere with the regulation modes in teaching and then we began to experience labor relationships with transience, in a short time, with precarious links and developing a performance in which the teacher will be suiting the rules in order to get a job vacancy. Thus, using an exploratory study we set out to observe the scene in which circumscribes the recruitment of teachers on temporary contracts and analyze the documents that legitimize the hiring process. The research was held in three phases, so that we could observe how candidates relate to the entry in public education through a selective hiring processes and the second and third phase, from the narratives of the teachers, show the developments in short-term work of the path that are configured in this universe of teachers on temporary terms. The research showed that the teachers on temporary contracts go through the experiences of competition among their peers to access a job vacancy, there is a weakness in the acceptance of these teachers in educational units and tensions start to be established at the end of the contract, which brings a sense of impotence before the logic of temporary contracts that have been naturalizing in teaching